UTILIZING A PROCESS MANAGEMENT APPROACH TO STANDARDISE THE APPLICATION OF VALUE STREAM MAPPING - Kuhlang, Peter (2011)
The systematic improvement of processes is practically realised in the industry and economy by operating a Process Management (PcM) System. Many authors also recommend a systematic repetition of Value Stream Mapping (VSM); but the global experiences in applying VSM do more or less indicate a single or punctual application of VSM to improve processes or value streams. The findings discussed in this paper describe the systematic embedding of Value Stream Mapping into the life cycle of a Process Management System using the principles of “innovation and continuous improvement”. Thus the Process Management System enables a systematic, regularly repeating application of VSM by extending its 4-Step-procedure. One suitable way to standardise the application of VSM is specified in this paper on a theoretical base to make this approach international applicable.